(untitled) (Patrimônio e Memória, 2016)
This article aims to study the always problematic relationship between literature and history. From some aspects of Hayden White’s last book, The Practical Past, we intend to question the fact thatsome historians, when they use literary material, ends up privileging a very specific genre, namely, the realist novel. In its end, this article also intends to demonstrate, through the woks of Antonio Candido and Franco Moretti, how the tools developed by the literary analysis can bring out historical meaning of non-realist novels.